2016
DOI: 10.1080/10962247.2016.1158133
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of nitric oxide decomposition efficiency achieved with lanthanum-based perovskite-type catalyst

Abstract: Direct decompositions of nitric oxide (NO) by La 0.7 Ce 0.3 SrNiO 4 , La 0.4 Ba 0.4 Ce 0.2 SrNiO 4 , and Pr 0.4 Ba 0.4 Ce 0.2 SrNiO 4 are experimentally investigated, and the catalysts are tested with different operating parameters to evaluate their activities. Experimental results indicate that the physical and chemical properties of La 0.7 Ce 0.3 SrNiO 4 are significantly improved by doping with Ba and partial substitution with Pr. NO decomposition efficiencies achieved with La 0.4 Ba 0.4 Ce 0.2 SrNiO 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…La-based perovskite oxides with La ions located in A-sites have been extensively investigated and applied in various applications [111][112][113][114][115][116], particularly in the catalysis of ORR [109,110,116]. For example, Sunarso et al [109] investigated the ORR activities of La-based perovskite oxides in alkaline media and reported that the increasing order of ORR activity for La-based perovskite oxides with different transition metal ions in B-sites was: LaCrO 3 < LaFeO 3 < LaNiO 3 < LaMnO 3 < LaCoO 3 .…”
Section: Non-precious Metal Catalystsmentioning
confidence: 99%
“…La-based perovskite oxides with La ions located in A-sites have been extensively investigated and applied in various applications [111][112][113][114][115][116], particularly in the catalysis of ORR [109,110,116]. For example, Sunarso et al [109] investigated the ORR activities of La-based perovskite oxides in alkaline media and reported that the increasing order of ORR activity for La-based perovskite oxides with different transition metal ions in B-sites was: LaCrO 3 < LaFeO 3 < LaNiO 3 < LaMnO 3 < LaCoO 3 .…”
Section: Non-precious Metal Catalystsmentioning
confidence: 99%
“…Various catalytic materials have been studied, such as precious metals [2][3][4], transition metal ion-exchanged zeolites [5][6][7], perovskites [8,9], and rare earth oxides [10,11]. Among them, the cobalt mixed oxides with a spinel structure represent the promising group of catalysts due to their good redox properties [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…There are many researches on praseodymium based materials, for example, to study the GMR properties of praseodymium based perovskites Pr 0.7 (Sr, Ca) 0.3 Mn 1−x Al x O 3 and Pr 0.5 Sr 0.5 Mn 1−x Al x O 3 17 , to study the catalytic properties of Pr 0.4 Ba 0.4 Ce 0.2 SrNiO 4 18 , and to study the relationship between thermal expansion and oxygen ion transport of A 1−a A a ’BO 3 perovskite-type oxides 19 .…”
Section: Introductionmentioning
confidence: 99%